Preparation of SiO2-Capped Sr2MgSi2O7:Eu,Dy Nanoparticles with Laser Ablation in Liquid - Mika Ishizaki; Takao Katagiri; Takao Sasagawa; Yoshitaka Kitamoto; Osamu Odawara; Hiroyuki Wada (Journal of Nanotechnology)
The effect of SiO2 capping on the optical properties of nanoparticles was investigated. The photoluminescence (PL) intensity was successfully improved by SiO2-capping. Sr2MgSi2O7:Eu,Dy nanoparticles were prepared by laser ablation in liquid. The SiO2 capping was performed using the Stöber method with ultrasonication. The TEM images indicated that the Sr2MgSi2O7:Eu,Dy nanocrystal was capped with amorphous SiO2, and the shape of the completely capped nanoparticle was an elliptical nanorod, which aggregated after a long SiO2 capping reaction time. The peak wavelength and the shape of the PL spectra were not changed by the pelletization and the laser ablation in liquid. The PL intensity of SiO2 capped nanoparticles was significantly increased. Nonradiative relaxation via surface defects and energy transfer to water molecules decrease the PL intensity. These phenomena accelerate in the case of nanoparticles. SiO2 capping would prevent these phenomena and improve the optical properties of nanoparticles. The combination of laser ablation in liquid and the chemical reaction is important to expand the applications of this method in various research fields.